Avaliação da influência da fonte de carbono sobre a expressão de genes associados à degradação da biomassa vegetal durante o cultivo do fungo Trichoderma Harzianum P49P11 em reator - Braga, Cleiton Márcio Pinto (2018)
Plant biomass is a renewable resource with great potential for obtaining a variety of products with different applications. The production of biofuels from vegetable biomass is an alternative to increase ethanol supply and thus meet the growing demand in the world. The lignocellulosic material, which makes up the biomass, consists mainly of cellulose, hemicellulose, pectin and lignin, which are arranged in a complex way, reflecting in the difficulty of material degradation. Several groups of enzymes need to be employed so that the complex carbohydrates are converted into fermentable sugars, which can then be transformed into interest products. However, the production costs of these biocatalysts are an obstacle to economic viability of the plant biomass biochemical conversion path. One of the mechanisms to reduce costs is the improvement of producing strains, for example, by the deletion of repressor genes and overexpression of activators related to cellulase production. For the fungus Trichoderma reesei, many works have identified such regulators as the activators xyr1, ace2, ace3 and lae1 and cre1 and ace1 repressors. But, the fungus T. harzianum lacks studies of this category, considering that it is pointed out as a good producer of cellulolytic enzymes. In order to better understand the dynamics of the genes associated with them, initially the profiles of these enzyme production and of regulatory genes (xyr1, ace1, ace2, cre1 and lae1) and hydrolases encoders expression were evaluated, along the bioreactor cultivation using different carbon sources. Expression was found to be significantly higher on cellulosic substrates, which also provided higher levels of enzymatic activity. In addition, a hydrolysis assay suggested that enzyme complex produced by the fungus was specific to the substrate that induced it. Finally, a strategy was set up for the fungus genetic improvement by means of a point mutation in the β-glucosidase cel1a gene.